Akhlak dalam Keluarga - Siti Rahmah (Alhadharah: Jurnal Ilmu Dakwah, 2021)
AbstractMorality in Islam is part of human nature, and the implication is that when applied, it will form humans who have good morals and can carry out their duties according to the purpose of human creation. The role of morality in the family is very crucial to form a sakinah mawaddah warahmah family. Each family member is expected to understand their respective positions by placing morals as a critical part of behavior, how to behave towards husband or wife, parents' morals towards children, and children's morals towards parents. So it is hoped that if this moral role is applied in all families, it will also impact the progress of a country.